Caregiver empowerment program based on the adaptation model increase stroke family caregiver outcome - Dharma Kelana Kusuma; Damhudi Dedi; Yardes Nelly; Haeriyanto Suhana (Sciendo, 2021)
Post-stroke disability and psychosocial disorders cause burdens for the families of stroke patients, including physical and financial burdens. The physical and psychological health of family caregivers determines the quality of care they provide to patients. The purpose of this study was to identify the effectiveness of the Caregiver Empowerment Program Based on the Adaptation Model (CEP-BAM) in increasing the family caregiver's coping ability against various problems and reducing their burden while caring for the stroke patient.